2017
DOI: 10.31237/osf.io/vpd8b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Learning to Doing: The Effects of Educating Individuals on the Pervasiveness of Bias

Abstract: Despite many trying to be egalitarian in social judgment, discrimination still occurs. One reason for the discrepancy between values and behavior may be the "bias blind spot" (Pronin & Kugler, 2007), which suggests that individuals more easily recognize bias in others than they recognize in themselves. Many people believe that they are objective and impartial and, as a consequence, falsely conclude that they are immune to biased judgments based on social group memberships. The purpose of this dissertation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Schein (1996) expanded on Lewin and identified "three processes necessary to achieve unfreezing, namely, disconfirmation of the validity of the status quo, the induction of guilt or survival anxiety and creating psychological safety" (Burnes, 2004, p. 985). Coming into an implicit bias training, people expect to be shamed or targeted (Ross, 2014), and extensive research has shown that shaming (Linnehan et al, 2003;Ross, 2014), "procedures that induced threat" (Forscher et al, 2017), divisive rhetoric (Dover et al, 2016), historical prejudice and assumed intentional bias (Von Bergen et al, 2002;Jackson and Joshi, 2011;Kalev et al, 2006;Joy-Gaba, 2011) do not work to change implicit bias behaviour. Instead, research from Devine et al (2012Devine et al ( , p. 1268 showed that motivation to "break the prejudice habit stems from two…”
Section: Unfreezeexamine Own Implicit Biasmentioning
confidence: 99%
“…Schein (1996) expanded on Lewin and identified "three processes necessary to achieve unfreezing, namely, disconfirmation of the validity of the status quo, the induction of guilt or survival anxiety and creating psychological safety" (Burnes, 2004, p. 985). Coming into an implicit bias training, people expect to be shamed or targeted (Ross, 2014), and extensive research has shown that shaming (Linnehan et al, 2003;Ross, 2014), "procedures that induced threat" (Forscher et al, 2017), divisive rhetoric (Dover et al, 2016), historical prejudice and assumed intentional bias (Von Bergen et al, 2002;Jackson and Joshi, 2011;Kalev et al, 2006;Joy-Gaba, 2011) do not work to change implicit bias behaviour. Instead, research from Devine et al (2012Devine et al ( , p. 1268 showed that motivation to "break the prejudice habit stems from two…”
Section: Unfreezeexamine Own Implicit Biasmentioning
confidence: 99%